Online Learning at Islamic Elementary School amidst Pandemic: Implementation, Challenges, and Key Success Factors - Zurqoni, Zurqoni; Saugi, Wildan; Abdillah, Muhamad Hasan; Susmiyati, Sri (Faculty of Education and Teacher Training of UINSI Samarinda, 2022)
This study aimed to explore the implementation of online learning at Madrasah Ibtidaiyah in East Kalimantan during the pandemic including its challenges and key success factors. This research was a field research with a qualitative approach. This research was conducted in Samarinda, Balikpapan, and East Kutai involving 9 (nine) Islamic elementary schools (MI) in East Kalimantan using simple random sampling techniques. Data collection techniques used interview, observation, and documentation. Data were then analyzed through data display, data condensation, and conclusion drawing/verification, and presented using descriptive techniques. The results revealed that the planning of learning was through the 2013 curriculum simplification, the simplification of the syllabus and lesson plans, online learning training for teachers, preparation of facilities and infrastructure, and socialization. The implementation of learning was done by determining the time, using the learning management system (LMS), determining the appropriate method and media, applying a variety of learning, and giving assignments and assessments. Evaluation was seen from student attendance that was 60%-95%, KKM that only reached 67%, the obstacles faced, as well as solutions or follow-up carried out by schools to minimize the problems. The challenges were how to provide equal facilities and infrastructure, increase teacher, parent and student digital literacy, and to create meaningful interaction during online learning. The key success factors of online learning implementation at MI included the availability of adequate gadgets, internet data and stable internet network, consistent collaboration between teachers and parents, and readiness of teachers and students.